Encouraging Critical Thinking Ability through Signs in Extensive Reading Class: Edusemiotics - Eni Faridah; Rukminingsih (ELITE JOURNAL, 2021)
The true challenge in academic setting is how to transform values and guide students’ mind growth with no excessive words. Thus, edusemiotics plays vital role and becomes a dominant in teaching and learning communication. Edusemiotics represents a new conceptual framework of theoretical study and the empirical one. This study aims at exploring how English Education Department students of 2017 A class STKIP PGRI Jombang elaborate ideas in interpreting signs on the picture to reflect their critical thinking ability. The data were taken from 10 students based on convenient sampling. This research performed qualitative method with a case study as research approach. Those students were in Extensive Reading class and asked to freely interpret the picture in accordance with their background of knowledge. There are three important findings; (1) students’ chosen picture, (2) students’ reading habit and personal experiences regarding with extensive reading, and (3) students’ critical thinking measurement and level. The result shows that 7 of students’ critical thinking level are in developing level while the 3 of students are in mastering level. Most of them basically have the reading habit before getting Extensive Reading program and it increases afterwards. The critical thinking ability is shown from how they elaborate ideas in interpreting sequence of signs on the picture and how they understand the values within. Keywords: critical thinking; extensive reading; social semiotic; multimodality; edusemiotics